ChemInform Abstract: 2", 4"‐O‐Diacetylquercitrin, a Novel Advanced Glycation End‐Product Formation and Aldose Reductase Inhibitor from Melastoma sanguineum. Issue 47 (4th November 2013) - Lee, Ik‐Soo; Kim, Il Soon; Lee, Yun Mi; Lee, Youngseop; Kim, Joo‐Hwan; Kim, Jin Sook
Abstract The novel flavonoid (I) is isolated from the aerial parts of M.sanguineum together with six known flavonoids.